La figura del padre en el teatro de Carlos Arniches - Falska, Maria (Romanica Silesiana)
This paper aims at examining the figure of the father in the dramas of Carlos Arniches, an author highly valued by directors, whose plays were frequently staged in Spain and Spanish America in the first half of the 20th century. Family relationships, and, above all, the figure of the father as a recurring element and an important dramatic motif in selected texts, are studied in detail. Among the father figures of Carlos Arniches there are: a despot father or a father-tyrant, an overindulgent father abused by his spendthrift family members, a father who sacrifices himself for the family, and a benevolent and spiritual father. In this article, these father figures are examined and classified according to their characteristic features, as well as the way in which they are introduced and how they function within the dramatic structure of the selected plays. This paper also offers an explanation of the ideological function of the author’s message conveyed by the analysed dramas.